What is quality in higher education? - Green, Diana M. (Buckingham : Society for Research into Higher Education & Open University Press, 1994)
It is a truism to say that whereas efficiency was the key word of the 1980s, quality is the touchstone of the 1900s. Concern about quality is not new in the educational context, although much of the debate outside of the sector has focused on standards.
Part 1. What is quality in higher education? -- Part 2. Models from within British higher education -- Part 3. Models from beyond British higher education.
Includes bibliographical references and index.
Keywords: EDUCATION